Neuronal Nicotinic Receptors Are Crucial for Tuning of E/I Balance in Prelimbic Cortex and for Decision-Making Processes - Pittaras, Elsa Cécile; Faure, Alexis; Leray, Xavier; Moraitopoulou, Elina; Cressant, Arnaud; Rabat, Arnaud Alexandre; Meunier, Claire; Fossier, Philippe; Granon, Sylvie (Frontiers in Psychiatry, 2016)
Rationale Decision-making is an essential component of our everyday life commonly disabled in a myriad of psychiatric conditions such as bipolar and impulsive control disorders, addiction and pathological gambling, or schizophrenia. A large cerebral network encompassing the prefrontal cortex -PFC- the amygdala and the nucleus accumbens is activated for efficient decision-making. Methods We developed a Mouse Gambling Task -MGT- well suited to investigate the influence of uncertainty and risk in decision-making and the role of neurobiological circuits and their monoaminergic inputs. Neuronal nicotinic acetylcholine receptors (nAChRs) of the PFC are important for decision-making processes but their presumed roles in risk-taking and uncertainty management, as well as in cellular balance of excitation and inhibition (E/I) need to be investigated. Results Using mice lacking nAChRs - β2-/- mice, we evidence for the first time the crucial role of nAChRs in the fine tuning of prefrontal E/I balance together with the PFC, insular, and hippocampal alterations in gambling behavior likely due to sensitivity to penalties and flexibility alterations. Risky behaviors and perseveration in extinction task were largely increased in β2-/- mice as compared to control mice, suggesting the important role of nAChRs in the ability to make appropriate choices adapted to the outcome.